MELUKIS MODEL SECARA ON THE SPOT MENGGUNAKAN OILPASTEL PADA KARYA PELUKIS JAYA ADI - Asviana Dwi Setyari (Universitas Negeri Malang, 2024)
Abstract: This study aims to determine: (1) Jaya Adi's background in painting (2) The process of making and the work created by painter Jaya Adi in painting models on the spot using oil pastel media. This research is a qualitative descriptive research method, using a single case study approach. The data sources used are Jaya Adi as the main informant and Sulistyo Hadinagoro as a believer. The event venue is at Jaya Adi Art Gallery, and the documents are in the form of articles and videos. The sampling technique used purposive sampling by taking a sample of 10 works by Jaya Adi based on his work on the spot. Data collection techniques used through in-depth interviews, direct observation, and document analysis. The validity test technique used is data source triangulation and informant review. The data analysis technique used is a flow model with data reduction steps, data presentation, and drawing conclusions. The results of the study can be summarized as follows: (1) Jaya Adi's journey in creating on the spot painting has an inspiration, namely M. Ifansyah, a portrait painter, then finds a creative process to paint portraits from his university days until now using oil pastels, in painting on the spot makes Jaya Adi confident and able to fulfill his inner needs or have his own satisfaction in creating when he gets various appreciations from people around him when he is doing the painting process. (2) The process of making a model painting includes: a) The model will be painted directly due to meetings at several events so that the model is selected based on fulfilling the criteria of a strong character in terms of being sweet or fierce or firm, there is also a desire for the model to be painted directly. b) The painting process includes determining the light intensity of the model with natural light from the sun or artificial light using a lamp, sketching the model framework and coloring details is done by reinforcing the anatomy of the model by considering dark and light as well as stroked lines to emphasize objects so as to form a volume, finishing is done by observing the model with the painting in depth followed by giving the identity of the painter. The pastel stroke techniques used in model painting are linear strokes, crossed strokes, removing color, and creating patterns. Painting models on the spot using oil pastels has been done by applying existing elements and principles of painting as well as pastel techniques. The painter can capture the character of each model he paints so that in his work he can produce paintings that are similar to the original model